2020
DOI: 10.1155/2020/8645869
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gas Explosion Injury Based on Analysis of Rat Serum Profile by Ultra‐Performance Liquid Chromatography/Mass Spectrometry‐Based Metabonomics Techniques

Abstract: Gas explosion can lead to serious global public health issues. Early period gas explosion injury (GEI) can induce a series of histopathologic and specific metabolic changes. Unfortunately, it is difficult to treat GEI thoroughly. To date, the specific molecular mechanism of GEI is still unclear. To accurately diagnose and provide comprehensive clinical intervention, we performed a global analysis of metabolic alterations involved in GEI. The physiological and behavioral indicators’ changes of rats after gas ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…By investigating the activities of the rate-limiting enzymes in the TCA cycle, specifically α-KGDH and ICDHm, the present study revealed that ATP content was decreased, and the TCA cycle was inhibited after the gas explosion. Similarly, a previous study demonstrated that the rapid consumption of energy by rats with gas explosion-induced injury downregulates galactose metabolism and the TCA cycle, both of which are consistent with the Warburg effect (6). In addition, the present study revealed that gas explosions not only inhibited oxidative phosphorylation but also affected glycolysis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…By investigating the activities of the rate-limiting enzymes in the TCA cycle, specifically α-KGDH and ICDHm, the present study revealed that ATP content was decreased, and the TCA cycle was inhibited after the gas explosion. Similarly, a previous study demonstrated that the rapid consumption of energy by rats with gas explosion-induced injury downregulates galactose metabolism and the TCA cycle, both of which are consistent with the Warburg effect (6). In addition, the present study revealed that gas explosions not only inhibited oxidative phosphorylation but also affected glycolysis.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have indicated that shock waves from a gas explosion contribute damage to the cavity viscera, such as the lungs and brain ( 27 , 28 ). The mechanism of gas explosion-induced lung injury is unclear, and our previous metabolomic study identified nine different metabolites that differ significantly between the control rats and explosion-induced acute lung injury rats ( 6 ). The identified biomarkers reflect well-known adverse health effects of a gas explosion, such as inflammation and impairment of glucose homeostasis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistically, damage in alveolar epithelial cells is the main cause of oxidative stress and inflammatory response, it plays an important role in blast wave-induced lung injury (15). Therefore, a lung injury model based on alveolar epithelial cell is particularly useful for mechanistic studies, especially considering the high cost and difficulties in energy control in establishing animal blast lung injury models (16). Herein, to establish a stable, reliable and flexible in vitro model, we exposed the alveolar epithelial cells with specified energies of blast wave and examined the appearance of blast injury.…”
Section: Introductionmentioning
confidence: 99%